Botanical garden as the cultural heritage object of Federal importance Separate historical data on materials of the cultural heritage object passport. Compliance with the requirements of legislation in the field of cultural heritage protection - Potemin, Michael (Hortus botanicus, 2018)
300 years-long development of the unique Botanical Garden complex in accordance with it’s historical functional purpose. Information on the condition of the Botanical Garden elements contained in the cultural heritage passport (2006). Observing the necessary measures in order to provide preservation of cultural heritage sites according to the requirements stated by the cultural heritage protection laws.